Faktor Eksternal dan Internal Yang Mempengaruhi Risiko Pembiayaan Pada Bank Umum Syariah - Fitriani Fitriani; Rahmi Syahriza; Nur Ahmadi Bi Rahmani (ITB AAS INDONESIA Surakarta, 2023)
This study sought to ascertain the impact of changes in the gross domestic product, inflation, currency rates, capital adequacy ratio, return on assets, operational expenses to operating revenues, and bank size on the financing risk (NPF) of Sharia Banks throughout. The secondary data used in this study is the financial statement of the Sharia Banks in Indonesia. Purposive sampling is the sampling technique employed in this study, and multiple linear regression analysis is the data analysis model. The findings of this study demonstrate that every internal and external bank element simultaneously affects the NPF. However, it partially demonstrated that external factors, such as inflation, currency rates, and increase in the gross domestic product, had no impact on the NPF. While internal bank data indicated that operational expenses to operating revenues and the capital adequacy ratio had no bearing on the NPF, return on assets and bank size did.